Identification and Molecular Characterization of Newcastle Disease Virus Circulates in some districts in Aceh - Daud AK, M; Setiyaningsih, Surachmi; Sudirman, Idwan (Universitas Syiah Kuala, 2019)
The objectives of this study were to assess the diversity of Newcastle Disease Virus (NDV) isolates; to detect and isolate NDV from poultry; and to identify and characterize NDV by serological and molecular assays. A total of 84 cloacal-oropharynx isolates of poultry was collected from privately owned poultries and poultry markets from 12 districts in Aceh Besar and Banda Aceh. Screening was performed by real time reverse transcriptation-polymerase chain reaction (rRT-PCR) to 15 isolates of poultry. Selected isolates were inoculated in 9-11 days old embryonated specific pathogen free (SPF) eggs and showed positive hemagglutination (HA). Characterization was performed through hemagglutination inhibition (HI) test using Komarov and Hitchner B1 antisera, elution test, RT-PCR and realtime RT-PCR fusion (F). All isolates had a higher affinity to Komarov antisera (titer up to 4 log), indicating virulent strain. This was supported by elution test which showed that 93.66% isolates were virulent and 6 % non-virulent. In conclusion, RT-PCR can detect Matrix gene from 15 isolates (100%), while Fusion gene only detected from 11 isolates (73.3%). rRT-PCR is more capable of detecting antigenic diversity compared to RT-PCR.